PENGARUH PENERAPAN MODEL PEMBELAJARAN GIVING QUESTIONS AND GETTING ANSWER TERHADAP HASIL BELAJAR SISWA KELAS X SMA N BANYUDONO TAHUN AJARAN 2011/2012 - Chasanah, Amalia; Santosa, Slamet; Ariyanto, Joko (P Biologi FKIP UNS Surakarta, 2012)
ABSTRACT ? This research is aimed to know effect of implementation strategy Giving Questions and Getting Answer (GQGA) towards biology learning achievement. This research held upon senior high school student of SMA N Banyudono in academic year 2011/2012. Giving Questions and Getting Answer (GQGA) was expected to be more effective rather than if use convensional method. All student of SMA N Banyudono had been chosen as a research population.Since, not all student was not attending biological class, hence, randomly, 2 clusters were selected representing the control class (for where the experimental treatment was not carried out) and the experimental class for where the Giving Questions and Getting Answer (GQGA). Quasy-experimental method was designed to achieve the stated research objectives following the quantitative paradigm used in this research. In addition, Randomized Subjects Posstest Only Control Group Design was used as a research design to facilitate the data collection procedures. The data were collected using several techniques namely, questionnaire, posttest with multiple choice, observation tools and related document. The final obtained data were then analyzed using t- test method. The results of this research showed that the implementation of the strategy has significantly affected the biology learning achievement. It has been proven to have an impact towards cognitive, affective and psychomotor aspects. Keywords: Giving Questions and Getting Answer (GQGA), Biology Learning Achievement